Immediate facial reanimation in oncological parotid surgery with neurorrhaphy of the masseteric-thoracodorsal-facial nerve branch. Issue 5 (June 2016) - Biglioli, Federico; Tarabbia, Filippo; Allevi, Fabiana; Colombo, Valeria; Giovanditto, Federica; Latiff, Mahfuz; Lozza, Alessandro; Previtera, Antonino; Cupello, Silvia; Rabbiosi, Dimitri
Abstract: The extracranial facial nerve may be sacrificed together with the parotid gland during a radical parotidectomy, and immediate reconstruction of the facial nerve is essential to maintain at least part of its function. We report five patients who had had radical parotidectomy (two with postoperative radiotherapy) and immediate (n = 3) or recent (n = 2) reconstructions of the masseteric-thoracodorsal-facial nerve branch. The first mimetic musculature movements started 6.2 (range 4–8.5) months postoperatively. At 24 months postoperatively clinical evaluation (modified House-Brackmann classification) showed grade V (n = 3), grade IV (n = 1), and grade III (n = 1) repairs. This first clinical series of masseteric-thoracodorsal-facial nerve neurorrhaphies has given encouraging results, and the technique should be considered as an option for immediate or recent reconstruction of branches of the facial nerve, particularly when its trunk is not available for proximal neurorrhaphy.